Awareness Regarding Cancer among People Residing in Kapilvastu District - Jyoti Priyanka,; Neelam Shrestha,; Amit Kumar Chaudhary,; Rubina Shrestha,; Gunjan Pokhrel,; Deepak Belbase, (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Cancer is a second leading cause of death globally, accounting for an estimate 9.6 million deaths or one in six in 2018 according to WHO factsheet. This study aimed to assess the awareness regarding cancer and its associated factors among adults of Maharajgunj Municipality of Kapilvastu. MATERIAL AND METHODS Community based, cross-sectional study design was conducted to assess the awareness regarding cancer and its associated factors and warning signs from January 2023 to July 2023, on a total of 400 participants in the age range of 20-90 years. Participants were enrolled in the study using simple random sampling technique. Data were collected using semi-structured questionnaire from consented participants. Chi-square test and binary logistic regression were used for further analysis. The level of signiﬁcance was set at p-value <0.05. RESULTS This study revealed that only 32.5% of participants were aware of symptoms and 32.8% of participants were aware of the risk factors associated with cancer. Signiﬁcant associations were found between cancer awareness of risk factors and socio-demographic variables such as occupation (p=0.049), education (p-value=0.02), religion (p-value=0.033), and ethnicity (p-value=0.016). However, this study showed statistically signiﬁcant association only between level of education and cancer awareness of symptoms. CONCLUSION The study ﬁndings indicate that approximately one-third of the participants had awareness regarding cancer risk factors and symptoms. These ﬁndings emphasize the urgent necessity for increased awareness of cancer among the community. Therefore, it is imperative to implement effective strategies to enhance community engagement in cancer-related health education programs.